PERSEPSI SISWA TERHADAP PROKRASTINASI AKADEMIK DAN IMPLIKASINYA DALAM LAYANAN BIMBINGAN DAN KONSELING DI SMA NEGERI 6 PADANG SEMESTER GENAP TAHUN AJARAN 2025/2026 - Cindy Amalia Fitri; Linda Fitria; Ridho Rismi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine student’s perceptions of academic procrastination and its implications for guidance and counseling services at SMA Negeri 6 Padang. This research used a quantitative descriptive method. The sample consisted of 262 students from grades X and XI, selected through proportional random sampling. The instrument was a Likert-scale questionnaire that had been tested for validity and reliability (α = 0.93). The results showed that the perception of grade X students towards academic procrastination was in the High category (60%), while grade XI students were in the Very High category (51%). The most dominant aspect of academic procrastination perception in both grades was the tendency to blame others. These findings imply the need for structured guidance and counseling services, such as information services, group guidance, individual counseling, and content mastery services. These services should be specifically designed to help students shift from an external to an internal locus of control, thereby reducing academic procrastination behavior and improving their learning effectiveness.